Efficiency of tooth bleaching agent on staining and discoloration characteristics of nicotine stained dental enamel model - Nattha Lertsukprasert; Kitsakorn Locharoenrat (BMC, 2020)
Abstract Background Surface staining and deeper discoloration characteristics of peroxide-based bleaching agents in the nicotine stain in dental enamel model were evaluated in the present study. Methods Nicotine stained dental enamel fragments (n = 36) were prepared and were subjected to the bleaching ingredients for a fixed treatment time of 30 min. The bleaching agents were composed of limonene, coconut diethanolamide, and carbamide peroxide served as solvent, nonionic surfactant, and oxidizer, respectively. Optical analysis was carried out considering color stability via colorimeter and UV-Vis spectrometer. Results Degrees of color variations were significantly influenced by nicotine content and bleaching ingredient factors. They varied in the range of approximately 3.00 and 5.00 units for all tooth-bleaching agents. The most prominent degrees of color variation elevations were obtained in the tooth bleaching formulae set #2 (1.0% limonene + 20% coconut diethanolamide) in the stained tooth model in comparison to set #1 (0.5% limonene + 10% coconut diethanolamide) and set #3 (1.5% limonene + 30% coconut diethanolamide), partly due to the perceptible color changes. The lowest degree of color variation under a dose limitation was found in the tooth bleaching formulae set #2 + 10% carbamide peroxide formulation. Absorbance spectra were also evaluated after the interaction of bleaching treatment. They confirmed a relationship between nicotine content and discoloration characteristics of the tooth bleaching formulae set #2 + 10% carbamide peroxide. Conclusions Carbamide peroxide is considered as generator of free radicals. It converts the color of stains to clear by oxidizing the organic compounds in the stained dental enamel model, achieving whiteness enhancement.